Association of hemoglobin glycation index with all-cause and cardio-cerebrovascular mortality among people with metabolic syndrome - Zhao, Leiyong; Li, Chengjun; Lv, Hequn; Zeng, Chunli; Peng, Yongjun (Frontiers in Endocrinology, 2024)
Background: Research on the association between blood glucose-related biomarkers and mortality has gained increasing attention. However, the association of hemoglobin glycation index (HGI) with all-cause and cardio-cerebrovascular mortality among people with metabolic syndrome has never been investigated. The objective of this study was to examine the association through a cohort study of the 2 American population.Methods: In this study, 8,267 participants were included. We utilized multivariable Cox regression analyses to explore the relationship between HGI and outcomes. The dose-response relationship between HGI and mortality was explored with restricted cubic splines. Recursive algorithms and segmented linear regression models were used to calculate the inflection points and assess the effect relationships before and after the inflection points.Results: In the model adjusting for all covariates, our analysis did not reveal a statistically significant association between HGI and mortality. Intriguingly, subsequent explorations of non-linear relationships unearthed a U-shaped correlation between HGI and both all-cause mortality and cardio-cerebrovascular mortality among American adults with metabolic syndrome. Before and after the inflection point, the HRs (95%CIs) for the association between HGI and all-cause mortality were 0.72 (0.63, 0.82) and 1.30 (1.17, 1.44), respectively. For cardio-cerebrovascular mortality, similar opposite relationships were found. The metabolic syndrome population with HGI levels at T2 had a lower rate of mortality.This cohort study of the American metabolic syndrome population highlighted a U-shaped association of HGI with all-cause and cardio-cerebrovascular mortality.